Expermental Studies of quantitative evaluation using HPLC - Ki Rok Kwon; Seong Bong Jang; Bae Chon Cha (Korean Pharmacopuncture Institute, 2005)
Methods : This study was conducted to carry out quantitative evaluation using HPLC Content analysis was done using HPLC Results : According to HPLC analysis, each BVA-1 contained approximately 0.36㎍ melittin, and BVA-2 contained approximately 0.54㎍ melittin. But the volume of coating was so minute, slight difference exists between each needle. Conclusion : Above results indicate that the bee venom acupuncture can complement shortcomings of syringe usage as a part of Oriental medicine treatment, but extensive researches should be done for further verification.